2021
DOI: 10.3390/ijms22052359
|View full text |Cite
|
Sign up to set email alerts
|

Derma-Hc, a New Developed Herbal Formula, Ameliorates Cutaneous Lichenification in Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic cutaneous disorder that is characterized by severe eczematous inflammation, swelling, and lichenification. Activation of T helper (Th)-22 cells by allergens leads to epidermal hyperplasia with hyperkeratosis at the chronic phase of AD. Derma-Hc is composed of five natural herbs with anti-AD effects, such as Astragalus membranaceus BUNGE, Schizonepeta tenuifolia Briq., Cryptotympana pustulata Fabr., Angelica sinensis Diels, Arctium lappa L. In this study, the ameliorative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…31,32 In a mouse model of AD, the transcription level of IL-22 was increased in secondary lesions with lichenification in which pSTAT3 also was detected. 33 Secondary lesions with a large number of pSTAT3positive keratinocytes in the present study showed a thickened epidermis (Figure 2c); therefore, the phosphorylation of STAT3 may have been induced by IL-22 in cAD, similar to the findings in the mouse model. Further studies are needed to investigate the role of IL-22 in the phosphorylation of STAT3 in cAD and its effect on epidermal proliferation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…31,32 In a mouse model of AD, the transcription level of IL-22 was increased in secondary lesions with lichenification in which pSTAT3 also was detected. 33 Secondary lesions with a large number of pSTAT3positive keratinocytes in the present study showed a thickened epidermis (Figure 2c); therefore, the phosphorylation of STAT3 may have been induced by IL-22 in cAD, similar to the findings in the mouse model. Further studies are needed to investigate the role of IL-22 in the phosphorylation of STAT3 in cAD and its effect on epidermal proliferation.…”
Section: Discussionsupporting
confidence: 84%
“…Interleukin‐22 is a cytokine that induces acanthosis in the chronic phase of AD 31,32 . In a mouse model of AD, the transcription level of IL‐22 was increased in secondary lesions with lichenification in which pSTAT3 also was detected 33 . Secondary lesions with a large number of pSTAT3‐positive keratinocytes in the present study showed a thickened epidermis (Figure 2c); therefore, the phosphorylation of STAT3 may have been induced by IL‐22 in cAD, similar to the findings in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…IgE secretion is increased in B cells by the Th2-mediated cytokine IL-4 [ 57 ], and the degranulation of mast cells by IgE increases itching through the release of histamine [ 27 , 58 ]. Continuous scratching can increase erythema, abrasions, and erosions, along with lichenification, which thickens the skin [ 59 , 60 , 61 ]. In addition, damage to the skin barrier caused by this scratching can further cause loss of moisture, leading to dry skin [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the skin gets thickened and leathery, which is known as 'lichenification', a severe symptom of AD (Nam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%